Drive on, thrive on - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Lennox Wilson A. Chitonga of Kaphiri Kamodzi Farm near Mwanza in Malawi is a smart farmer. He tells of the transformation of one hectare of dry, useless land into thriving farmland. The farm is situated west of Middle Shire river. The area used to...